The Effect of Lidocaine Gel on Pain Perception During Diagnostic Flexible Cystoscopy in Women: A Randomized Control Trial. Issue 2 (March 2019) - Dougher, Erin; Zoorob, Dani; Thomas, Diane; Hagan, Joseph; Peacock, Lisa
Abstract : Objective: The objective of this study was to determine if there is a clinically meaningful variation in pain perception when using lidocaine gel versus plain lubricant prior to office-based diagnostic flexible cystoscopy. Methods: This was a randomized, controlled, double-blind trial comparing lidocaine gel and water-based lubricant for the performance of diagnostic flexible cystoscopy. Women undergoing cystoscopy were randomized to either transurethral 2% lidocaine (Uro-Jet) or water-based lubricant prior to cystoscopy. Participants and physicians were blinded, and pain was assessed using an 11-point numeric rating scale (NRS). A priori sample size calculation indicated the need for 40 patients per group to achieve 90% power. Descriptive statistics and Student t test were utilized. Results: The study included 116 patients, 61 in the lidocaine group and 55 in the plain lubricant group. Numeric rating scale in the lidocaine group (2.43 [SD, 1.95]) was significantly lower than that in the plain lubricant group (3.58 [SD, 2.73]) ( P = 0.01). After controlling for age and ethnicity, separately as well as together, the procedural NRS scores were 1.37 points ( P = 0.002), 0.97 points ( P = 0.04), and 1.22 points ( P = 0.01) lower in those receiving lidocaine. After the procedure, fewer patients in the lidocaine group (2/61 = 3.3%) requested pain medicine when compared with the plain lubricant group (11/55 = 20%) ( P = 0.01). Although anticipated pain scored similarly between groups, actual pain compared with anticipated pain was significantly lower in the lidocaine group ( P = 0.02). Conclusions: Pain perception during flexible cystoscopy decreased when using 2% transurethral lidocaine gel. The use of 2% lidocaine gel is suggested for the reduction of pain at the time of diagnostic flexible cystoscopy in women.